Assessing students’ continuance intention in using multimedia online learning - Taqwa Hariguna; Akmal Akmal (Universitas Ahmad Dahlan, 2019)
The study aimed to assess the students’ continuance intention (SCI) in using multimedia online learning including students’ perceived usefulness (SPU), students’ ease of use (SPE), and students’ flow experience (SFE). There is no,so far, the assessment of students’ activity in using multimedia online learning within the extended Technology Acceptance Model (TAM).This study revealed the students’ continuance intentions in using online lessons.There were 523 students as the samples. They learned and examined the content of online English learning resources as well as multimedia aspects.TAM was used to predict the SCI. The results indicate that the students’ intentions are influenced positively by perceived usefulness, ease of use, and the flow experience. The SPU influenced more students’ motivation than SPE. It is recommended that designers of online learning should be more specific in determining target users. The online learners’ skill on ICT, pedagogical principles, and technological barrier in different region are among the determinant aspects for receiving positive enduring intention.